(untitled) (Research, Society and Development, 2023)
The demand for specialty coffees on the world market is growing, and their commercial value is directly linked to their quality. When subjected to ultraviolet (UV) light, some raw coffee beans show a blue fluorescence. Around the world, producers and traders have used UV light as a quality analysis method to detect defects in beans that cannot be seen with the naked eye. Despite being a technique used for a long time, almost no scientific study has been done to confirm and clarify the matter. Therefore, the work aims to evaluate the quality of the beans that emit and do not emit fluorescence from the same batch. For this, a batch of natural specialty coffee was divided into treatments with different fluorescence concentrations and analyzed sensorially and physicochemically. It was observed that the increase in fully fluorescent beans concentration negatively affected the coffee final score and astringency, and the increase in partially fluorescent beans concentration negatively affected the final score, astringency, sweetness, acidity, bitterness, and aftertaste of the coffee. Furthermore, attributes such as fruity notes and sweetness were affected by the presence of fluorescence, thus changing the sensory profile. In the physicochemical analyses, a reduction in the coffee quality was observed for the parameters of potassium leaching, electrical conductivity, fatty acidity, polyphenols, titratable acidity, moisture and weight of 1000 seeds. Therefore, it was possible to observe that the use of UV light to assess the green coffee beans quality can be a viable method.